2021
DOI: 10.1111/jfpp.16044
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐assisted vacuum drying as alternative drying method to increase drying rate and bioactive compounds retention of raspberry

Abstract: This study aimed to determine the effect of different drying methods, namely hot air drying (HAD), vacuum drying (VD), ultrasound-assisted vacuum drying (USVD), and freeze drying (FD) on drying kinetic, total phenolic antioxidant activity, anthocyanin profile, in vitro-bioaccessibility of phenolic and color quality of raspberry samples. The drying time of the raspberry was 540, 720, and 1,140 min for USVD, VD, and HAD, respectively, indicating that USVD showed a significantly lower drying time than VD and HAD.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 53 publications
4
14
0
Order By: Relevance
“…Dry matter accumulation and excessive shrinkage on the product surface during the drying period may have caused an undesirable change in the deterioration of the porosity structure (Panyawong & Devahastin, 2007). The deterioration of the porous structure of the samples dried with HAD was reported in other studies (An et al, 2022; Tekin Cakmak et al, 2021). In the samples dried with IRD, it is seen that the pore structure is mostly lost and the pore diameters are noticeably reduced.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…Dry matter accumulation and excessive shrinkage on the product surface during the drying period may have caused an undesirable change in the deterioration of the porosity structure (Panyawong & Devahastin, 2007). The deterioration of the porous structure of the samples dried with HAD was reported in other studies (An et al, 2022; Tekin Cakmak et al, 2021). In the samples dried with IRD, it is seen that the pore structure is mostly lost and the pore diameters are noticeably reduced.…”
Section: Resultssupporting
confidence: 75%
“…Larger pore diameters were observed in the FD-treated samples. This indicated that the of the samples dried with HAD was reported in other studies (An et al, 2022;Tekin Cakmak et al, 2021). In the samples dried with IRD, it is seen that the pore structure is mostly lost and the pore diameters are noticeably reduced.…”
Section: Effect On Rehydration Ratio and Microstructural Propertiessupporting
confidence: 82%
“…The SEM images of the dried blueberries are given in Figure . As seen, the blueberry samples were partially damaged by HAD and underwent tissue breakage . The blueberry samples with UAVD showed more porosity and open structure compared to those with VD because of lower drying time and cavitation effects led to evaporation of water on the inner surface .…”
Section: Resultsmentioning
confidence: 91%
“…The higher degradation occurred in samples dried with HAD. This could be due to the long drying time and high thermal load, resulting in significant anthocyanin losses in the HAD and VD, and technique . FD exhibited the highest anthocyanin content, followed by UAVD.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is carrot tissue was investigated. The authors of [18] investigated the effect of different drying methods (hot air drying, vacuum drying, ultrasound-assisted vacuum drying and freeze drying) on drying kinetics and quality of raspberry samples. USVD showed a significantly lower drying time than VD and HAD.…”
Section: Introductionmentioning
confidence: 99%